Effects of a single session of transcranial direct current stimulation on static balance in a patient with hemiparesis: a case study - Ferreira, Luiz Alfredo Braun; Galli, Manuela; Oliveira, Claudia Santos; Lazzari, Roberta Delasta; Dumont, Arislander Jonathan Lopes; Santos, Cibele Almedia; Carvalho, Debora Bachin; Renata Calhes Franco de Moura; Araujo, Maria Carolina (Journal of Physical Therapy Science, 2015)
[Purpose] Cerebrovascular accident (stroke) is characterized by an abrupt onset of focal or global neurological signs and symptoms. Asymmetry of the limbs is common following a stroke due to hemiplegia or hemiparesis. [Subject and Methods] A male patient having suffered an ischemic stroke was initially evaluated using the Timed Up-and-Go Test and the Six-Minute Walk Test. Static balance was evaluated using a force plate (Kistler model 9286BA) for the stabilometry analysis of center of pressure (COP) sway. The data were interpreted using the SWAY software program (BTS Engineering) synchronized with the SMART-D 140® system. Anodal transcranial direct current stimulation (tDCS; 2 mA) was applied over the primary motor cortex for 20 minutes during gait training on a treadmill. [Results] Under the condition of eyes open, reductions were found in anteroposterior sway (6.18%), trace length (3.3%) and sway velocity (3.3%) immediately following tDCS. [Conclusion] A single session of anodal tDCS combined with treadmill training had a positive effect on the static balance of a subject with chronic hemiparesis stemming from a stroke.